2013
DOI: 10.1097/wno.0b013e3182594001
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Acetazolamide During Pregnancy in Intracranial Hypertension Patients

Abstract: There is no convincing evidence for an adverse effect for acetazolamide use in human pregnancy, even when prescribed prior to the 13th week of gestation. While the liberal use of acetazolamide should be avoided during pregnancy, this medication should remain a treatment option in pregnant women when clinically indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 23 publications
0
66
0
3
Order By: Relevance
“…14,15 In our opinion, as with all medications given to pregnant women, acetazolamide should remain a treatment option if the risk of progressive visual loss is sufficiently high to warrant its use.…”
Section: Diureticsmentioning
confidence: 97%
See 2 more Smart Citations
“…14,15 In our opinion, as with all medications given to pregnant women, acetazolamide should remain a treatment option if the risk of progressive visual loss is sufficiently high to warrant its use.…”
Section: Diureticsmentioning
confidence: 97%
“…Several reports do not recommend the use of acetazolamide during pregnancy because of potential teratogenicity effects. 14,15 Acetazolamide was thus classified as class C according to the Food and Drug Administration (FDA), indicating that animal studies have shown an adverse effect; however, there are no adequate and well-controlled studies on pregnant women.…”
Section: Diureticsmentioning
confidence: 99%
See 1 more Smart Citation
“…And the incidence is increasing in parallel with the current worldwide epidemic of obesity [14,15]. Although considerable literature has been published concerning IIH occurred during pregnancy [16,17] and childhood [18,19], there are few studies reported IIH occurred after spinal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we are in agreement with the suggestion of Al-Saleem and Al-Jobair1 regarding the verification of the absence of pregnancy before initiating acetazolamide to women of reproductive age. Nevertheless, the successful use of acetazolamide has been described in a limited number of pregnant women with intracranial hypertension 6,7. As previously remarked by Falardeau et al, clinicians should be aware that “The avoidance of acetazolamide during the first trimester has very little medical justification and is mainly guided by medical–legal rationale” 7.…”
mentioning
confidence: 99%